An update on the improvement of patient eligibility with the use of new generation endografts for the treatment of abdominal aortic aneurysms. (1st November 2020) - Kontopodis, Nikolaos; Galanakis, Nikolaos; Tzartzalou, Ifigeneia; Tavlas, Emmanouil; Georgakarakos, Efstratios; Dimopoulos, Ioannins; Tsetis, Dimitrios; Ioannou, Christos V
ABSTRACT: Purpose: Endovascular aneurysm repair (EVAR), performed within device instructions for use (IFU), offers improved outcomes. New endograft designs attempt to increase eligibility rates of abdominal aortic aneurysm (AAA) patients treated within device IFU. We aim to examine the anatomic suitability of the Ovation endograft in our AAA patients and compare it with the other contemporary devices. Research design and methods: Three-hundred and seven consecutive elective AAA patients treated during a 5-year period were included. Patient-specific anatomic characteristics were based on endograft IFUs to determine eligibility rates of each system. Results: Two-hundred-twenty-five patients underwent EVAR and 82 open surgery. Ineligibility for device implantation was significantly lower for the Ovation iX system (32%) compared to other devices (AFX-2:49%, Altura:49%, Anaconda:54%, Endurant II:46%, Excluder:52%, Excluder Conformable:39%, Incraft:43%, E-Tegra:52%, Zenith-Alpha:52%; P-Value<0.001). The Alto system (next-generation Ovation) achieved an even lower ineligibility rate of 30% (P = 0.008). Short proximal aortic neck length followed by access vessel inadequacy were the primary reasons for ineligibility. Conclusion: The Ovation-iX included more patients with anatomic characteristics within device IFUs resulting in improved eligibility rates compared with the rest of contemporary devices. Its evolution, the Alto system, further improves patient eligibility due to the inclusion of shorter aortic necks. Expert Opinion: The Ovation iX system presented a significantly better performance and was eligible for use in a greater number of patients in our series of elective AAA repairs, accommodating patient-specific aortic anatomies. Of course, performing EVAR within the endograft's IFU is important to achieve optimal and durable outcomes. The proximal neck length followed by the size of the access vessels are the two more common factors resulting in loss of eligibility. Except for overall eligibility rates, a case by case decision must be made on which is the most suitable device for each patient, based on the specific characteristics of its unique anatomy.